Lagrangian Timescales of Southern Ocean Upwelling in a Hierarchy of Model Resolutions. Issue 2 (31st January 2018) - Drake, Henri F.; Morrison, Adele K.; Griffies, Stephen M.; Sarmiento, Jorge L.; Weijer, Wilbert; Gray, Alison R.
Abstract: In this paper we study upwelling pathways and timescales of Circumpolar Deep Water (CDW) in a hierarchy of models using a Lagrangian particle tracking method. Lagrangian timescales of CDW upwelling decrease from 87 years to 31 years to 17 years as the ocean resolution is refined from 1° to 0.25° to 0.1°. We attribute some of the differences in timescale to the strength of the eddy fields, as demonstrated by temporally degrading high‐resolution model velocity fields. Consistent with the timescale dependence, we find that an average Lagrangian particle completes 3.2 circumpolar loops in the 1° model in comparison to 0.9 loops in the 0.1° model. These differences suggest that advective timescales and thus interbasin merging of upwelling CDW may be overestimated by coarse‐resolution models, potentially affecting the skill of centennial scale climate change projections. Plain Language Summary: In this paper we use a variety of ocean models to investigate how long it takes for deep ocean waters to upwell to the surface of the Southern Ocean around Antarctica. We track virtual particles in our simulated currents and show how they spiral southward and upward toward the surface. We find that this journey takes 87 years in a standard coarse‐resolution climate model but only 17 years in a state of the art high‐resolution climate model. We argue that the difference between the models is due to vortices which vigorously upwell the virtual particles but are too small to be represented in standard climate models. Particles also only loop around Antarctica 0.9 times in the high‐resolution model compared to 3.2 times in the coarse‐resolution model, suggesting that different kinds of upwelling waters have less time to mix with each other in coarse‐resolution models. These differences in timescale and the number of loops suggest that there exist biases in long‐term climate change projections using standard coarse‐resolution climate models. Key Points: The timescales and 3‐D structure of Circumpolar Deep Water (CDW) upwelling are missing from the zonally integrated overturning framework Lagrangian transit times of upwelling CDW are longer with coarser grid spacing or longer temporal averaging of the sampled velocity field As horizontal model resolution increases, particles complete fewer circumpolar loops thereby limiting interbasin merging of CDW